PENGARUH KECEMASAN MATEMATIKA DAN SELF CONCEPT SAAT PANDEMI COVID-19 TERHADAP HASIL BELAJAR MATEMATIKA SISWA - Bagus Tri Atmojo; Ibrahim Ibrahim (Universitas Sultan Ageng Tirtayasa, 2021)
Covid-19 has spread in Indonesia from March 2020 until now, bringing significant changes to many fields, one of which is education. Learning activities that were previously carried out face-to-face, are now being online. Of course, conditions like this have an impact on mathematics learning outcomes and can stimulate anxiety instability and self-concept in students. Therefore, this research intends to obtain: 1) the negative effect of math anxiety during the COVID-19 pandemic on student mathematics learning outcomes, 2) the positive effect of self-concept during the COVID-19 pandemic on student mathematics learning outcomes, and 3) the effect of math anxiety and self-concept during the COVID-19 pandemic simultaneously regarding student mathematics learning outcomes. This research method is correlational with a quantitative approach. The sample subjects in this research were 30 students of class X in SMA Negeri 3 Bantul. The selection of sample subjects used a simple random sampling method. The instruments used in this research were the Likert scale and the final assessment of the first semester of the 2020/2021 school year. The data analysis used is multiple regression analysis. The results of this research conclude that there is a negative and significant effect of mathematics anxiety on mathematics learning outcomes as indicated by the regression coefficient, 0.465. Then, this research also concludes that there is a positive and significant effect of self-concept on mathematics learning outcomes as indicated by the results of the regression coefficient, 0.617. Finally, this research concludes that there is a significant influence on math anxiety and self-concept simultaneously on mathematics learning outcomes as indicated by the coefficient of determination, 70.6%.